2022
DOI: 10.1002/jmv.27564
|View full text |Cite
|
Sign up to set email alerts
|

Novel putative pathogenic viruses identified in pangolins by mining metagenomic data

Abstract: The pangolin is the only scaly mammal in the world and also an important reservoir of pathogenic viruses. Habitat loss and poaching have been shrinking the survival range of pangolins. More information on pangolin virus populations is needed to better understand and assess potential disease risks. In this study, viral metagenomic data were used to reinvestigate the virome in pangolin lung tissue. Complete genome sequences of two novel anelloviruses were acquired and clustered with the referenced feline strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It also contains the conserved domains expected in functional retroviruses, although the terminal end of the env gene is missing (either from true truncation or incomplete assembly). The virus is most closely related to AdCPG/aus/1 sampled from the lung tissue of Malayan pangolins (Ning et al, 2022). BLASTn analysis of the complete genome of AdCPG/aus/1 showed the absence of this genome in any bat reference genome on NCBI/GenBank.…”
Section: Resultsmentioning
confidence: 99%
“…It also contains the conserved domains expected in functional retroviruses, although the terminal end of the env gene is missing (either from true truncation or incomplete assembly). The virus is most closely related to AdCPG/aus/1 sampled from the lung tissue of Malayan pangolins (Ning et al, 2022). BLASTn analysis of the complete genome of AdCPG/aus/1 showed the absence of this genome in any bat reference genome on NCBI/GenBank.…”
Section: Resultsmentioning
confidence: 99%
“…Previous virome investigations of diseased pangolins have focused on vertebrate-hosted viruses, including Reoviridae , Parvoviridae , Papillomaviridae , Circoviridae , Flaviviridae , and Picornaviridae ( Liu et al, 2019 ; Ning et al, 2022 ; Yang et al, 2021 ). In this study, we provided more detailed information and confirmed that these viruses are carried by healthy pangolins.…”
Section: Discussionmentioning
confidence: 99%
“…By using data mining approaches, Feng Z et al suggested identifying additional suspected harmful viruses in pangolins. They found two genomes of the genus Gemykibivirus and nine types of bat-associated circovirus, respectively [11]. With the implementation of five distinct text different classifiers that perform well in tweet categorization, Rahman R presented a real-time Twitter data mining method for inferring user mobile perceptions [12].…”
Section: Related Workmentioning
confidence: 99%